INNOVATIVE LEARNING TECHNOLOGIES AND THEIR ROLE IN THE EDUCATIONAL PROCESS IN HUMANITIES - Yatsyshyn, Mykhailo; Bondaruk, Liudmyla; Horot, Alla; Hunchyk, Iryna; haichevska, Tetiana; Koropatnitska, Tetiana (AD ALTA-JOURNAL OF INTERDISCIPLINARY RESEARCH, 2023)
Innovative technologies in education in humanities make it possible to regulate learning and direct it in the right direction. Stereotypes in the mass consciousness affecting the habitual way of life, lead to painful phenomena and hinder the renewal of all types of education. The reason for the reluctance of people to accept innovations in modern education lies in the blocking of vital needs for comfort, security, and self-affirmation. Innovative behavior does not imply adaptation; it presupposes the formation of one's individuality and self-development. The teacher must understand that innovative education is a way of educating a pleasant personality. "Ready-made templates " are not suitable for him; constantly improving his intellectual level is essential. A teacher who has got rid of "complexes, " psychological barriers, is ready to participate fully in innovative transformations. One of the tasks of the modern humanitarian school is to unlock the potential of all participants in the pedagogical process and to provide them with opportunities to display their creative abilities. The solution to these problems is only possible by implementing the variability of educational approaches, in connection with which various innovative types and educational institutions require deep scientific and practical understanding.
Keywords: Digital generatione-Learning, Humanities, Information and communication technologies, Innovative learning, Modern education system, Online courses